The Effects Of Adipic Acid On The Hydrophobicity IPP Membranes Prepared Using Dpe Via Tips - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; Rosmawati, Naim (Asian Research Publishing Network (ARPN), 2016)
Over the past few decades, global expansions of industrial activities significantly has increased the concentrations of some gases in the atmosphere, such as Carbon Dioxide (CO2) from flue gas, which tend to warm the earth’s surface. One of the technology is gas separation using membrane can remove the CO2 from flue gas to prevent the danger of global warming. However, in the flue gas, there is water vapour content that causes the membrane to swell.Thus, for this study, in order to increase the durability and performance of membrane for CO2/N2 separation, the hydropobic membrane is purposed. This study focuses on the effect of the addition of adipic acid on the hydrophobicity of the isotactic Polypropylene (iPP) membranes. The results show that membrane prepared without addition of adipic acid produces highest contact angle, CO2 permeability and selectivity which are 112°, 22.01 GPU and 1.59 respectively. For morphology by using Scanning Electron Microscopy (SEM), observation on the increasing adipic acid shows increasing in pore size and the pore size distribution.